The pedigree of baraitric surgery: A case series of revisional surgery post laparoscopic sleeve gastrectomy in 3 sisters - AlSabah, Salman (Int J Surg Case Rep, 2018)
INTRODUCTION: Obesity is a complex disease involving multiple factors that play a role in its development, including genetics. Given the high prevalence of obesity in Kuwait, this is of particular interest. CASE: This is a case of 3 sisters that presented to a single surgeon for morbid obesity with starting body mass indexes (BMI) of 46.9 kg/m(2),56 kg/m(2),and 51.3 kg/m(2). All three elected to undergo a laparoscopic sleeve gastrectomy as an initial procedure. They presented to thier surgeon 5.5 years later with weight regain. The first patient elected to undergo a Laparoscopic Re-Sleeve Gastrectomy, the second Roux-en-Y Gastric Bypass, and the third Single-Anastomosis Gastric Bypass. The patients were followed up for 2-years post-revisional, for which the % EWL was 35.5%, 48.4% and 25.2%, respectively. CONCLUSION: Our study was also able demonstrate how effective revisional surgery is, when genetics are accounted for, with our results showing RYGB as a revisional procedure being superior to the other options.